Electrophysiological basis of reading related phonological impairment in Chinese speakers with schizophrenia: An ERP study. (30th March 2017) - Wang, Jiuju; Liu, Qi; Wydell, Taeko N.; Liao, Jinmin; Wang, Fang; Quan, Wenxiang; Tian, Ju; Wang, Pengfei; Liu, Jin; Dong, Wentian
Abstract: It has been reported in alphabetic languages that individuals with schizophrenia showed language-related cognitive impairments including phonological deficits, which were in turn associated with clinical symptoms such as auditory hallucinations and thought disorders. To date, however, the phonological deficits involved in schizophrenia in Chinese and its neural basis have not been well established. In order to establish such a relationship we conducted a behavioral study using lexical tone judgment and digit span tasks as well as an event-related potential (ERP) study with an auditory oddball paradigm, in particular, for P300 effects, the event-related brain potential (ERP) index of discrimination. Chinese patients with schizophrenia and Chinese healthy controls in China participated in the current study. Compared to the healthy controls, the patients with schizophrenia showed significant impairments in phonological processing skills, which in turn significantly correlated with smaller P300 effects. Thus these behavioral and electrophysiological findings in Chinese patients with schizophrenia were critically evaluated in terms of their phonological processing abilities. Highlights: Chinese patients with schizophrenia showed impaired phonological processing skills. Chinese patients with schizophrenia showed reduced P300 effects. The reduction of P300 effects may be the underlying electrophysiological basis of phonological deficits.